The rebellious man: Next-of-kin accounts of the death of a male relative on antiretroviral therapy in sub-Saharan Africa. Issue 9 (2nd September 2019) - Skovdal, Morten; Ssekubugu, Robert; Nyamukapa, Constance; Seeley, Janet; Renju, Jenny; Wamoyi, Joyce; Moshabela, Mosa; Ondenge, Kenneth; Wringe, Alison; Gregson, Simon; Zaba, Basia
ABSTRACT: The HIV response is hampered by many obstacles to progression along the HIV care cascade, with men, in particular, experiencing different forms of disruption. One group of men, whose stories remain untold, are those who have succumbed to HIV-related illness. In this paper, we explore how next-of-kin account for the death of a male relative. We conducted 26 qualitative after-death interviews with family members of male PLHIV who had recently died from HIV in health and demographic surveillance sites in Malawi, Tanzania, Kenya, Uganda, Zimbabwe and South Africa. The next-of-kin expressed frustration about the defiance of their male relative to disclose his HIV status and ask for support, and attributed this to shame, fear and a lack of self-acceptance of HIV diagnosis. Next-of-kin painted a picture of their male relative as rebellious. Some claimed that their deceased relative deliberately ignored instructions received by the health worker. Others described their male relatives as unable to maintain caring relationships that would avail day-to-day treatment partners, and give purpose to their lives. Through these accounts, next-of-kin vocalised the perceived rebellious behaviour of these men, and in the process of doing so neutralised their responsibility for the premature death of their relative.